Design and Implementation of a Solar Panel–Based Backup Energy Supply System for an Egg Incubator in Jatijejer Village, Mojokerto - Reza Sarwo Widagdo; Ardianik Ardianik; Ratna Hartayu; Imam Suri Tauladan; Puji Slamet; Aris Heri Andriawan (Perkumpulan Kualitama Edukatika Indonesia, 2026)
Power supply reliability is a critical factor in the hatchery industry, as egg incubator machines require continuous and stable electrical energy to maintain optimal temperature and humidity conditions throughout the incubation period. In many rural areas, including Jatijejer Village, Mojokerto, East Java, Indonesia, frequent power outages from the main electricity grid often disrupt incubator operation, causing temperature fluctuations that can reduce hatchability rates and negatively affect poultry productivity. These conditions highlight the need for a reliable backup energy solution to ensure uninterrupted incubation processes. To address this challenge, this study implements a small-scale solar photovoltaic (PV) system as a backup power supply for a semi-automatic egg incubator installed in Desa Jatijejer, Mojokerto. The proposed backup energy system consists of a 20 Wp solar panel, a 10 A solar charge controller, and a 12 V 12 Ah battery as the primary energy storage unit. With an available energy capacity of approximately 144 Wh, the battery is capable of supplying power to a low-consumption egg incubator during temporary grid outages. This capability is particularly important during critical stages of embryonic development, where stable temperature conditions are essential to ensure successful hatching. The PV–battery configuration is designed to function as an emergency backup system rather than a long-term replacement for the main grid, thereby maintaining incubation continuity during short-duration electrical disturbances. In addition to technical implementation, this study evaluates partner perceptions through a satisfaction survey involving 20 respondents from the local poultry farming community. The survey results indicate a high level of satisfaction with the implemented system, reflected by an overall mean score of 4.37 out of 5. The suitability of the technology achieved a mean score of 4.30, while system performance obtained a mean score of 4.35. Ease of operation and maintenance recorded a mean score of 4.25, suggesting good usability with potential for minor improvement. The highest satisfaction scores were observed for service team responsiveness and overall satisfaction, both reaching 4.45, while training clarity achieved a mean score of 4.40. Overall, the findings confirm that the solar PV backup system enhances incubator reliability and supports sustainable poultry production in rural areas with unstable electricity supply.